N‐glycan maturation mutants in Lotus japonicus for basic and applied glycoprotein research. (22nd May 2017) - Pedersen, Carina T.; Loke, Ian; Lorentzen, Andrea; Wolf, Sara; Kamble, Manoj; Kristensen, Sebastian K.; Munch, David; Radutoiu, Simona; Spillner, Edzard; Roepstorff, Peter; Thaysen‐Andersen, Morten; Stougaard, Jens; et al.
Summary: Studies of protein N ‐glycosylation are important for answering fundamental questions on the diverse functions of glycoproteins in plant growth and development. Here we generated and characterised a comprehensive collection of Lotus japonicus LORE1 insertion mutants, each lacking the activity of one of the 12 enzymes required for normal N ‐glycan maturation in the glycosylation machinery. The inactivation of the individual genes resulted in altered N ‐glycan patterns as documented using mass spectrometry and glycan‐recognising antibodies, indicating successful identification of null mutations in the target glyco‐genes. For example, both mass spectrometry and immunoblotting experiments suggest that proteins derived from the α1, 3‐fucosyltransferase ( Lj3fuct ) mutant completely lacked α1, 3‐core fucosylation. Mass spectrometry also suggested that the Lotus japonicus convicilin 2 was one of the main glycoproteins undergoing differential expression/ N ‐glycosylation in the mutants. Demonstrating the functional importance of glycosylation, reduced growth and seed production phenotypes were observed for the mutant plants lacking functional mannosidase I, N ‐acetylglucosaminyltransferase I, and α1, 3‐fucosyltransferase, even though the relative protein composition and abundance appeared unaffected. The strength of our N ‐glycosylation mutant platform is the broad spectrum of resulting glycoprotein profiles and altered physiological phenotypes that can be produced from single, double, triple and quadruple mutants. This platform will serve as a valuable tool for elucidating the functional role of protein N ‐glycosylation in plants. Furthermore, this technology can be used to generate stable plant mutant lines for biopharmaceutical production of glycoproteins displaying relative homogeneous and mammalian‐like N ‐glycosylation features. Significance Statement: Protein N ‐glycosylation is an important post‐translational modification. To study the structure and function of this heterogeneous modification in vivo, tools to elucidate the importance of this modification in complex biological systems are needed. Here we present a platform containing null mutants for each of the 12 catalysing enzymes in the N ‐glycosylation maturation pathway. This tool also provides a potential expression system for glycoprotein therapeutics displaying customised or mammalian‐like N ‐glycosylation patterns.